The therapeutic effect of phellopterin on colitis-associated cancer and its effects on TLR4/NF-κB pathway and macrophage M2 polarization: Effect of phellopterin on colitis-associated cancer - Xu, Xiaoping; Su, Yue; Pan, Yuan; Shen, Minmin; Liu, Daochen; Liu, Zhaohui; Chen, Dong; Wu, Jia (Cellular and Molecular Biology, 2023)
This study was conducted to investigate the effect and mechanism of phellopterin on colitis-associated cancer (CAC). For this purpose, CAC mouse model was established by AOM/DSS method, and the therapeutic effects of phellopterin in different doses were compared. The levels of interleukin-6 (IL-6), IL-1β, IL-10, and tumor necrosis factor-α (TNF-α) in peripheral blood were detected by ELISA. The changes in T lymphocyte subsets and the expressions of CD163, CD206, Arg-1, and Ym-1 in colonic macrophages were detected. The expression of TLR4 and NF-κB p65 in the colon was tested by Western blot. Results showed that as against the Model group, the body weight and survival rate of mice treated with phellopterin were increased, the disease activity index, hematochezia rate, and tumor formation rate were decreased, the colon length was increased, and the number of tumors and spleen index were decreased (P<0.05). As against the Model group, the proportion of CD4+ and CD8+ in the peripheral blood of phellopterin intervention mice increased, the content of IL-6, IL-1β, and TNF-α decreased, and the content of IL-10 increased. The expression of CD163, CD206, Arg-1, and Ym-1 in colonic macrophages was decreased. The protein expressions of TLR4 and NF-κB p65 in colon tissue were decreased (P<0.05). The effect of phellopterin intervention on CAC was dose-dependent. In conclusion, phellopterin can improve the symptoms and inflammatory response of CAC and inhibit the occurrence of colon cancer (CC) by inhibiting M2 polarization of macrophages and activation of the TLR4/NF-κB pathway.